2003
DOI: 10.1039/b300887h
|View full text |Cite
|
Sign up to set email alerts
|

Ag8Cl2[Se2P(OEt)2]6: A rare example containing a combination of discrete clusters and chainsElectronic supplementary information (ESI) available: analytical data for compounds 1 and 2. See http://www.rsc.org/suppdata/cc/b3/b300887h/

Abstract: The novel halide-centered Ag(I)8 cubic clusters containing diethyl diselenophosphato ligands are prepared and their solid state structures, a discrete unit or a one-dimensional chain, are dictated by the counter anions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 19 publications
(8 reference statements)
0
11
1
Order By: Relevance
“…The P−Se distances average 2.158 Å. The Se···Se “bite” distances average 3.757 Å and are slightly shorter than those (3.805−3.818 Å) found in the Ag 8 cube . The remaining three, where hinge positions are the heights of the prism, are each capped by a triply bridging iodide atom over an alternating set of three of the six triangular faces (Figure b).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The P−Se distances average 2.158 Å. The Se···Se “bite” distances average 3.757 Å and are slightly shorter than those (3.805−3.818 Å) found in the Ag 8 cube . The remaining three, where hinge positions are the heights of the prism, are each capped by a triply bridging iodide atom over an alternating set of three of the six triangular faces (Figure b).…”
Section: Resultsmentioning
confidence: 90%
“…Several cubic clusters encapsulating S 2- , Cl - , and Br - are known for a dithiophosphate ligand . For the corresponding diselenophosphate ligands, our research group has reported selenide-centered cubes, [Cu 8 (μ 8 -Se){Se 2 P(O i Pr) 2 } 6 ] 8 and [Ag 8 (μ 8 -Se){Se 2 P(O i Pr) 2 } 6 ], as well as halide-centered cubes, [Cu 8 (μ 8 -X){Se 2 P(OR) 2 } 6 ](PF 6 ) 10 and [Ag 8 (μ 8 -X){Se 2 P(OR) 2 } 6 ](PF 6 ) (X = Cl, Br) . Recently, we have reported a novel nonacoordinated selenide in a tricapped trigonal-prismatic geometry in a Cu 11 cluster where 11 copper atoms adopt a pentacapped trigonal-prismatic geometry. 10b, Clusters or cages having the geometry of a pentacapped trigonal prism are not common .…”
Section: Introductionmentioning
confidence: 99%
“…Four coordination modes of diselenophosphates have been identified in their metal complexes (II−V, Chart ), and mode I is being reported for the first time in this paper. In view of our interest to develop coordination chemistry of diselenophosphates as ligands and also after finding very interesting polynuclear complexes with Cu I , Ag I , and Zn II , we were curious to look into main group elements.…”
Section: Introductionmentioning
confidence: 77%
“…Four coordination modes of diselenophosphates have been identified in their metal complexes (II−V, Chart ), and mode I is being reported for the first time in this paper. In view of our interest to develop coordination chemistry of diselenophosphates as ligands and also after finding very interesting polynuclear complexes with Cu I , Ag I , and Zn II , we were curious to look into main group elements. In this respect, indium(III) formed octahedral, tris-chelated complexes, In[Se 2 P(OR) 2 ] 3 , which in solution state showed lability of the In−Se bonds, and in order to explore the generality of this observation, we were interested in investigating the interaction of dsep ligands with group 14 metals.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation